2017
DOI: 10.1007/s10815-017-1040-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pregnancy outcomes after vitrification at the cleavage and blastocyst stage: a meta-analysis

Abstract: In summary, this meta-analysis shows that vitrification at any stage has no detrimental effect on clinical outcome. Blastocyst transfer will still remain a favorable and promising option in ART. Due to the small sample evaluated in the pool of included studies, large-scale, prospective, and randomized controlled trials are required to determine if these small effects are clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
20
1
Order By: Relevance
“…In patients with frozen embryo transfer, the transfer of blastocyst was an independent predictor of clinical pregnancy after adjustment for confounders, supporting the superiority of blastocyst transfer for IVF success in frozen cycles. The data in the literature do not uniformly support our results, a recent meta-analysis showing that CPR is similar in transfers of frozen blastocysts or cleavage-stage embryos [17]. In turn, other authors showed that frozen blastocyst transfer is superior to cleavage-stage embryo transfer in both poor and normal responders [18].…”
Section: Resultscontrasting
confidence: 99%
“…In patients with frozen embryo transfer, the transfer of blastocyst was an independent predictor of clinical pregnancy after adjustment for confounders, supporting the superiority of blastocyst transfer for IVF success in frozen cycles. The data in the literature do not uniformly support our results, a recent meta-analysis showing that CPR is similar in transfers of frozen blastocysts or cleavage-stage embryos [17]. In turn, other authors showed that frozen blastocyst transfer is superior to cleavage-stage embryo transfer in both poor and normal responders [18].…”
Section: Resultscontrasting
confidence: 99%
“…Because more embryos are achieved on day 3 in group 2, culturing embryos to blastocyst stage for transfer is a good option. Day 5–6 embryos have lower rate of segmental aneuploidy (19) and higher viability for implantation (20) than day 2–3 embryos. Preimplantation genetic testing for aneuploidies (PGT-A) are also beneficial for advanced women to select an euploid embryo to transfer (21).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been voiced that the stage of freezing may not exert an impact on the implantation success rate or the clinical pregnancy rate. On a recent meta-analysis, the clinical pregnancy rate between vitrification warming cycles on cleavage or blastocyst stage poses no difference (Risk Ratio 0.97, 95% Confidence Interval) despite the fact that the implantation rate was higher for the blastocyst transfers [32].…”
Section: Discussionmentioning
confidence: 99%